Enhanced Solubility and Oral Bioavailability of γ‐Tocotrienol Using a Self‐Emulsifying Drug Delivery System (SEDDS). Issue 8 (17th June 2014) - Alqahtani, Saeed; Alayoubi, Alaadin; Nazzal, Sami; Sylvester, Paul W.; Kaddoumi, Amal
Abstract: The aim of this study was to evaluate the in vitro and in vivo performance of γ‐tocotrienol (γ‐T3) incorporated in a self‐emulsifying drug delivery system (SEDDS) and to compare its enhanced performance to a commercially available product, namely Tocovid Suprabio™ (hereafter Tocovid), containing tocotrienols. The solubilization of γ‐T3 was tested in a dynamic in vitro lipolysis model followed by in vitro cellular uptake study for the lipolysis products. In addition, in vitro uptake studies using Caco2 cells were conducted at different concentrations of γ‐T3 prepared as SEDDS, Tocovid, or mixed micelles. γ‐T3 incorporated in SEDDS or Tocovid was orally administered to rats at different doses and absolute oral bioavailability from both formulations were determined. The dynamic in vitro lipolysis experiment showed about two fold increase in the solubilization of γ‐T3 prepared as SEDDS compared to Tocovid, which correlated with higher cellular uptake in the subsequent uptake studies. In vitro cellular uptake and in vivo oral bioavailability studies have shown a twofold increase in the cellular uptake and oral bioavailability of γ‐T3 incorporated in SEDDS compared to Tocovid as a result of improvement in its solubility and passive uptake as confirmed by in vitro studies. In conclusion, incorporation of γ‐T3 in SEDDS formulation enhanced γ‐T3 solubilization and passive permeability, thus its cellular uptake and oral bioavailability when compared to Tocovid.